1986
DOI: 10.1111/1365-3040.ep11616247
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of alternating‐temperature regimes that remove seed dormancy in seeds of Brachiaria humidicola (Rendle) Schweickerdt

Abstract: Seeds of Braehiaria humidieola were subjected, on a thermogradient plate, to a wide range of alternating-temperature cycles (24 h) and constant temperatures with intermittent exposure to diffuse laboratory light, in the presence and absence of 10 mol m"-^ KNO3. The optimum regime for maximum percentage germination was alternating temperatures of 35 °C for 4hd"' and 13"C for 20 h d"'. Almost no germination occurred at any constant temperature. Thermoperiods in which the warmer temperature was applied for the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The temperature that promotes the highest germination percentage and rate is referred to as the optimum temperature. In the natural habitat, seeds germinate under alternating temperature regimes, and various studies on the effects of alternating temperatures on seed germination have found that seeds of some species germinate only at alternating temperature regimes (Harrington 1923;Morinaga 1926;Goedert and Roberts 1986;Ellis and Barret 1994;Kebreab and Murdoch 1999;Baskin and Baskin 2001).…”
mentioning
confidence: 99%
“…The temperature that promotes the highest germination percentage and rate is referred to as the optimum temperature. In the natural habitat, seeds germinate under alternating temperature regimes, and various studies on the effects of alternating temperatures on seed germination have found that seeds of some species germinate only at alternating temperature regimes (Harrington 1923;Morinaga 1926;Goedert and Roberts 1986;Ellis and Barret 1994;Kebreab and Murdoch 1999;Baskin and Baskin 2001).…”
mentioning
confidence: 99%